Overview of erythritol production by yeast strains - Khatape, Anil B.; Dastager, Syed G.; Rangaswamy, Vidhya (Fems Microbiology Letters, 2022)
Erythritol is a 4-carbon polyol produced with the aid of microbes in presence of hyper-osmotic stress. It is the most effective sugar alcohol that is produced predominantly by fermentation. In comparison to various polyols, it has many precise functions and is used as a flavor enhancer, sequestrant, humectant, nutritive sweetener, stabilizer, formulation aid, thickener, and a texturizer. Erythritol production is a common trait in a number of the yeast genera viz., Trigonopsis, Candida, Pichia, Moniliella, Yarrowia, Pseudozyma, Trichosporonoides, Aureobasidium, and Trichoderma. Extensive work has been carried out on the biological production of erythritol through Yarrowia, Moniliella, Candida, and other yeast strains, and numerous strategies used to improve erythritol productivity through mutagenesis and genetic engineering are discussed in this review.
Keywords: Erythritol; erythrose reductase; hyperosmotic stress response; metabolic pathways; Yeast; yeast expression

Strain improvement for enhanced erythritol production by Moniliella pollinis Mutant-58 using jaggery as a cost-effective substrate - Khatape, Anil B.; Rangaswamy, Vidhya; Dastager, Syed G. (International Microbiology, 2024)
Erythritol has been produced by various microorganisms including Yarrowia, Moniliella, Aureobasidium, and Candida strains. Due to its relatively high price, erythritol sweetener is used lesser than other polyols despite having many advantages. Therefore, in this study, Moniliella pollinis strain was improved for erythritol production by chemical mutagenesis and subsequently screening for cost-effective carbon sources for the enhanced erythritol yield. M. pollinis was subjected to N-methyl N-nitro N-nitroso guanidine (NTG), ethyl methyl sulfonate (EMS), and UV mutagenesis for improved erythritol production. The fmutant strains were evaluated for enhanced erythritol production medium optimization by using different carbon substrates at the shake flask level. To enhance the production of erythritol and statistical media, optimization was carried out using a central composite design (CCD). Among 198 isolated mutants, Mutant-58 strain generated by EMS mutagenesis was selected for further assessment. The Mutant-58 strain showed significant morphological changes as compared to the parent strain. Furthermore, statistically optimized media composition resulted in the higher production of erythritol (91.2 & PLUSMN; 3.4 g/L) with a yield of 40.7 & PLUSMN; 3.4 % in shake flask experiments. The optimized medium composition for erythritol production constitutes (g/L) 225 jaggery, 4.4 yeast extract (YE), 4.4 KH2PO4, 0.31 MgSO4, and pH 5.5. The present study demonstrated strain improvement, media, and process optimization resulting in a 30% increase in the erythritol production in the Mutant-58 as compared to the parent strain. This is also the first instance where jaggery has been used as a cost-effective carbon source alternative to glucose for industrial-scale erythritol production.
Keywords: Erythritol; Fermentation; Moniliella pollinis; Mutation; Optimization; renewable resource

Advances in metabolic engineering and fermentation for 3-hydroxypropionic acid biosynthesis: a comprehensive review - Joshi, Harshvardhan; Isar, Jasmine; Rangaswamy, Vidhya; Raghunathan, Anu (World Journal of Microbiology & Biotechnology, 2025)
The grand challenge in biobased Manufacturing Lies in achieving the sustainable, economically competitive conversion of renewable biomass into high-value Chemicals capable of replacing fossil-derived products. Among these, 3-hydroxypropionic acid (3-HP) has emerged as a top-tier target-an exceptionally versatile platform molecule. It finds applications in the synthesis of acrylic acid, 1,3-propanediol, and other derivatives, positioning it as a potential cornerstone for bio-based plastics. This review consolidates the latest breakthroughs in microbial 3-HP production, encompassing advanced strain engineering, pathway rewiring, cofactor optimization, metabolic modeling, and flux balance analysis. We critically examine strategies to overcome inherent metabolic and physiological constraints, including byproduct suppression, redox balancing, and tolerance engineering. Emerging approaches-such as dynamic regulation of metabolic flux, control of cell morphology and density, and integration of co-production pathways-are highlighted for their capacity to boost yields and process robustness. Additionally, we address the fermentation process innovations targeting enhanced productivity, substrate efficiency, minimal nutrient input, and industrially relevant titres. Collectively, these insights Chart a clear path toward the scalable, sustainable biomanufacturer of 3-HP.
Keywords: 1; 3-hydroxypropionaldehyde; 3-hydroxypropionic acid; 3-Propanediol; Fermentation; flux balance analysis; Metabolic engineering